ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN HALMAHERA UTARA - Pangerapan, Thressa Resita; Karamoy, Herman; Alexander, Stanly W. (Universitas Sam Ratulangi, 2018)
Local Own Revenue (PAD) is regional income derived from the results of local taxes, the results of local retribution, the result of separated regional wealth management, and others. The purpose of this study, to determine the effectiveness and contribution to the North Halmahera District's Original Revenue. The analytical method used is descriptive qualitative that is analyzing the level of effectiveness and contribution from data realization of Hotel Tax District of North Halmahera. The results showed that (1) the effectiveness of Hotel Tax in 2013 until 2017 experienced a decrease and a varied increase. The highest effectiveness is in 2014 with the percentage of 116.08% and included in the criterion is very effective, then the lowest effectiveness is in 2016 with the percentage of 86.32% and included in the criterion less effective, (2) Hotel Tax Contribution on 2013 to 2017 goes into very less criteria. And that included in the lowest criterion number is in 2015 with a percentage of 1.82%.Keywords: Local Original Income, Effectiveness, Contribution